Peptide self-assembled nanomedicine induces antitumor immunity by blocking the PD-1/PD-L1 axis - Huang, Tao; Sun, Xianfu; Meng, Xiaocao; Chen, Mengdie; Li, Yapeng; Du, Shengnan; Qi, Yingqiu; Ge, Hong (Frontiers in Materials, 2022)
The development of Immune checkpoint inhibitors (ICIs) revolutionize cancer treatment, which has been applied in the treatment of several kinds of malignancies in the clinic. Due to the specific affinity and controllable cost, the emerging peptide-based ICIs therapeutics have attracted great attention. However, peptide-based drugs generally show poor bioavailability and a short in vivo half-life. Peptide-based nanomedicine is a promising approach to increase the efficacy of therapeutic peptides. In this work, an amphiphilic peptide based on the reported D peptide for ICIs has been developed. The constructed amphiphilic peptide can self-assemble into a stable nanostructure (noted as CD-NPs). The prepared CD-NPs have a spherical shape with a hydrodynamic size of about 35 nm. In vivo studies show that the prepared nanomedicine can effectively inhibit tumor growth in 4T1 tumor-bearing mice. Moreover, we find that the CD-NPs increase the infiltration of effector T cells and natural killer cells as well as the immune cytokines in the tumor tissues, implying they activated the immune response for anti-tumor activity. Finally, no obvious changes in the major organs tissues or the body weight caused by the nanomedicine can be observed, demonstrating their good biocompatibility. Taken together, this study provides a basic idea for designing novel peptide-based nanomedicine for enhanced antitumor efficacy by enhancing the blockade of ICIs and activating the immune response.